(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article shows that personal adjectives in English can acquire a positive or negative meaning with prefixes. Although the number of adjective-forming affixes in English is small, the combination possibilities of these few affixes are wider than in Uzbek. In the Uzbek language, the number of quality-forming affixes is more than 50, but some of these affixes are considered mutually meaningful. However, it is stated that these synonyms cannot be used as alternatives to each other. With or without affective changes, these tools can be used in the sentence as determiners, complements, possessors and participles.